Residue determination of phenthoate in tomato fruits - Raetano, Carlos Gilberto; de Batista, Gilberto Casadei (Pesquisa Agropecuaria Brasileira, 1995)
The objective of the present research was to study the degradation and the persistence of phenthoate (Elsan 50 CE) residues in tomato fruits. The experiment was set in a tomato field located in Mombuca, State of São Paulo, Brazil, after 45 days from seedlings transplantation. Dosages of 600 (A), 800 (B), 1200 (C) and 1600 g a.i./ha (D) were sprayed at the beginning of the ripening period of fruits. Samples of 15 fruits each were collected 1, 4, 10, 20 and 40 days after products spraying. The utilized procedure consisted of extraction with acetone and purification by partition with dichloromethane. The purified extract was concentrated and injected into a gas chromatograph equipped with alkaly flame ionization detector (AFID). The limits of detection were of 0,01 ppm for this product. The recovery percentage from fortified samples varied from 60 to 81%. The degradation and the persistence half-lives were 1 to 2 and 3 to 6 days for phenthoate, respectively.